Home-based interactive rehabilitation system for hand - Jee Chen Hung, C. (Institute of Electrical and Electronics Engineers Inc., 2017)
A hand home-based rehabilitation system which is interactive, portable and affordable, equipped with the ability in qualitative and quantitative diagnosis on muscle performance and strength is reported in this paper. The therapy system utilizes the concept of game-based therapy which aims to develop interest of patient. The hardware input module has a compact joypad input design with wireless connectivity to promote portability. The system is designed using open-source platform, Adobe Flash Builder. The system introduces activities which is task oriented or with basic games which is derived from Fugl-Meyer Assessment (FMA) for the purpose of assessing muscle performance. The final design also includes the ability to diagnose muscle strength using electromyography measurement test (EMG). © 2016 IEEE.